Subacute two stage metatarsal lengthening with gradual distraction for brachymetatarsia: A consecutive case series and literature review. Issue 1 (January 2023) - Hung, Wei-Chen; Chen, Chun-Ho; Lin, Chang-Hao; Chen, Tzu-Yin; Lo, Sheng-Pin
Abstract: Background: This study examined the functional and clinical outcomes of subacute two stage metatarsal lengthening with gradual distraction for brachymetatarsia. This technique was developed to overcome the disadvantages of one-stage metatarsal lengthening and gradual distraction. Methods: Four feet of three patients with congenital brachymetatarsia underwent subacute two stage metatarsal lengthening with gradual distraction. Pain, function, and alignment were assessed preoperatively and at follow-ups using the American Orthopaedic Foot and Ankle Society (AOFAS) lesser metatarsophalangeal–interphalangeal scale, and any complications were recorded. Results: The patients were followed up for a mean of 18.1 ± 6.9 (range, 12.6–28.1) months. The mean metatarsal length gain was 15.2 ± 3.2 (range, 12.1–18.5) mm, and the corresponding percent increase was 32.5 % ± 7.0 % (range, 25.7–41.1 %). The mean AOFAS score (0−100) was 97.5 ± 5.0 at the final follow-up. The external fixator index was 10.2 ± 1.5 (range, 8.1–11.6) days/cm. None of the patients experienced metatarsophalangeal stiffness, subluxation or dislocation of the metatarsophalangeal joint, loss of correction, pin tract infection, delayed union, nonunion, or angular deformities. Conclusion: Subacute two stage metatarsal lengthening with gradual distraction is a reliable alternative treatment for brachymetatarsia.